2007
DOI: 10.1007/s10535-007-0110-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional gene silencing is involved in resistance of transgenic papayas to papaya ringspot virus

Abstract: Transgenic papayas carrying the papaya ringspot virus coat protein gene were inoculated with Papaya ringspot virus. Infection was monitored by evaluating symptoms and by reverse transcription polymerase chain reaction (RT-PCR). Among eight tested transgenic lines, clone G2 was found highly resistant to virus infection during 3 years of testing. Further analysis of this clone revealed complex multicopy transgene insertion with aberrant copies. The suspected post transcriptional gene silencing was confirmed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Other studies have shown that the absence of transgene homology with the challenge virus CP gene does not always correlate with ability of a PRSV strain to breakdown resistance in transgenic papaya (Chen et al ., 2002; Ruanjan et al ., 2007; Tripathi et al ., 2004; Yeh et al ., 2003). Agro‐transformation of papaya with the CP gene of a native Taiwanese isolate, PRSV YK (Cheng et al ., 1996), showed good resistance in several field trials from 1996 to 1999 (Bau et al ., 2003, 2004a).…”
Section: Control Strategies: Conventional To Genetically Engineered Rmentioning
confidence: 99%
“…Other studies have shown that the absence of transgene homology with the challenge virus CP gene does not always correlate with ability of a PRSV strain to breakdown resistance in transgenic papaya (Chen et al ., 2002; Ruanjan et al ., 2007; Tripathi et al ., 2004; Yeh et al ., 2003). Agro‐transformation of papaya with the CP gene of a native Taiwanese isolate, PRSV YK (Cheng et al ., 1996), showed good resistance in several field trials from 1996 to 1999 (Bau et al ., 2003, 2004a).…”
Section: Control Strategies: Conventional To Genetically Engineered Rmentioning
confidence: 99%
“…A strong silencing suppressor could potentially help to break genetically engineered virus resistance [6,7]. Thus, if the HcPro of one isolate were more effective than the HcPro of another isolate in suppressing the RNA silencing, the earlier would be expected to replicate better than the latter in PRSV-resistant plants [5].…”
Section: Prsv-hcpro Affects Micro Rna Biology By Sequestering Themmentioning
confidence: 99%
“…However, the field evaluation with geographically distinct PRSV isolates was not very encouraging. Later, reports have shown, that the sequence divergence of the virus from the transgenes does not always correlate with the ability to overcome virus resistance [5], an involvement of RNA silencing suppressor seems to be more likely the main factor involved in breaking of PRSV transgenic resistance [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The differences between geographically distinct isolates have made the creation of PRSV-resistant transgenic plants difficult. The failure of PRSV resistance has frequently involved the silencing by suppressor proteins of viral origin [ 73 ]. This problem can be overcome by the silencing suppressor protein HcPro, through an RNA-silencing mechanism within transgenic papaya.…”
Section: Gene Technology For the Development Of Prsv-resistant Tramentioning
confidence: 99%